Respuesta :

Answer:

(7,-2)

Step-by-step explanation:

You can solve this using the substitution method by:

x - y = 9

2x + y = 12

Let's take the first equation:

x - y = 9

Add y to both sides:

x = 9 + y

Then use this as a value in the other equation:

2 ( 9 + y ) + y = 12

Distribute and simplify:

18 + 2y + y = 12

18 + 3y = 12

Subtract 18 from both sides:

3y = -6

Divide each side by 3:

y=-2

Then use this value in one of the equations to get the other value:

x + y = 9

x + ( -2 ) = 9

Rearrange this to make it easier:

9 - 2 = x

7 = x

(7,-2) is your answer

Hope this helps!

Answer:

(7,-2)

Step-by-step explanation:

7 = X

ACCESS MORE